Development and testing of the situational judgement test to measure safety performance of healthcare professionals: An explorative cross‐sectional study. Issue 1 (1st November 2021) - Heier, Lina; Gambashidze, Nikoloz; Hammerschmidt, Judith; Riouchi, Donia; Geiser, Franziska; Ernstmann, Nicole
Abstract: Aim: To measure safety performance, situational judgement test, which is a method composed of job‐related situations, can be used. This study aimed to develop and test its psychometric properties by measuring the safety performance of healthcare professionals in German hospitals. Design: An explorative cross‐sectional study. Methods: A team of researchers, nurses and physicians developed seven items, which focus on different safety areas. Descriptive statistics were calculated for each item. Cronbach's alpha was calculated as an indication of internal consistency. Spearman's correlation between the items was evaluated as analysis of construct validity. A cross‐sectional survey with healthcare professionals in three German hospitals was conducted to test the developed instrument. Results: A total of 168 healthcare professionals participated (response rate: 39.1%). 70.2% were women, and 38.7%, 33.9%, 15.5% and 11.3% were registered nurses, nurses in training, physicians and other healthcare professionals respectively. The situational judgement test demonstrated an acceptable psychometric performance.